2017
DOI: 10.1039/c7ta06341e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production with ultrahigh efficiency under visible light by graphene well-wrapped UiO-66-NH2 octahedrons

Abstract: The proposed electrons transfer mechanism for graphene well-wrapped UiO-66-NH2 octahedrons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 37 publications
3
37
0
1
Order By: Relevance
“…Both of them have no photocatalytic hydrogen production activity under visible light (k > 400 nm). In addition, UiO-67-Ce MOF outperforms the previously reported Zr-based MOF photocatalysts in the photocatalytic hydrogen evolution reaction [51,53,54]. All of the above confirms that the introduction of bpydc-Ce into UiO-67 can greatly improve the photocatalytic hydrogen evolution from water.…”
Section: Photocatalytic Performancesupporting
confidence: 61%
“…Both of them have no photocatalytic hydrogen production activity under visible light (k > 400 nm). In addition, UiO-67-Ce MOF outperforms the previously reported Zr-based MOF photocatalysts in the photocatalytic hydrogen evolution reaction [51,53,54]. All of the above confirms that the introduction of bpydc-Ce into UiO-67 can greatly improve the photocatalytic hydrogen evolution from water.…”
Section: Photocatalytic Performancesupporting
confidence: 61%
“…In addition, MOFs, specifically, NH 2 ‐MIL‐101, NH 2 ‐MIL‐125(Ti), Cu‐BTC, NH 2 ‐MIL‐88B(Fe), UiO‐66, and ZIF‐8, have been used as host matrices for anchoring g‐C 3 N 4 to fabricate g‐C 3 N 4 ‐based composites with improved photocatalytic performance, which is due to increased chemical heterogeneity as well as efficient interfacial charge transfer from photoexcited g‐C 3 N 4 to MOFs . For example, UiO‐66‐NH 2 , a Zr‐containing MOF constructed of zirconium‐oxo clusters and aminoterephthalates, has a highly chemically stable, flat surface and, thus, has been used as a popular host matrix for dispersing metal and semiconductor nanoparticles for water splitting . However, to date, the application of UiO‐66‐NH 2 covered with g‐C 3 N 4 to derive ZrO 2 /g‐C 3 N 4 heterostructures for H 2 production by water splitting has not been reported in the literature.…”
Section: Introductionsupporting
confidence: 81%
“…The work confirmed that the Pt NPs inside the MOFs could shorten the electron‐transfer distance and achieve fast inner electron transfer to Pt for producing hydrogen. Actually, in our previous work, we reported another efficient way to achieve the separation of electrons and holes by using graphene to wrap UiO‐66‐NH 2 octahedrons and provide more transfer directions for electrons near graphene, which could efficiently inhibit the recombination of electron–hole pairs. However, for the electrons inside the MOF crystals, the recombination of generated electron and holes that are far from the outer graphene cannot be suppressed because the transfer distance is too long.…”
Section: Methodsmentioning
confidence: 99%
“…Efficiencies of 1.01 and 0.86 %w ere obtained for 500 and 550 nm as the ErB dyes had as trong adsorption in the range of 480-560 nm. [9] Even at 600 and 700 nm, the quantum efficienciesc ould reach up to 0.60 % and 0.02 %o wing to the enhanced light-harvesting ability.…”
mentioning
confidence: 99%